1994
DOI: 10.1177/027836499401300204
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Walking of a Vehicle With Two Telescopic Legs Controlled by Two Drives

Abstract: This article describes a walking vehicle with two telescopic legs that was designed at the Institute of Mechanics at Moscow University. The vehicle is driven by two DC drives. Its con trol system comprises a computer, hardware servosystems, and power amplifiers. An adaptive algorithm has been developed for control of vehicle locomotion. This algorithm is based on the tracking of the commanded path. A part of the path is planned by the computer in advance using a mathematical model of the vehicle. The rest is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…The pendulum's length was varied so as to maintain the biped's COM at a constant height above the walking surface. To control walking in a three-link, three-DOF planar biped with telescoping legs, Grishin et al [94] used PID control to track precomputed trajectories that were subsequently modified online to improve stability. To control walking in a planar, five-DOF biped, Mitobe et al [156] used computed torque to regulate the biped's COM and swing leg end position.…”
Section: Control Of Bipedal Locomotionmentioning
confidence: 99%
“…The pendulum's length was varied so as to maintain the biped's COM at a constant height above the walking surface. To control walking in a three-link, three-DOF planar biped with telescoping legs, Grishin et al [94] used PID control to track precomputed trajectories that were subsequently modified online to improve stability. To control walking in a planar, five-DOF biped, Mitobe et al [156] used computed torque to regulate the biped's COM and swing leg end position.…”
Section: Control Of Bipedal Locomotionmentioning
confidence: 99%
“…To take into account this problem and to ensure the biped reaches its final desired configuration at the impact, the reference trajectories of the actuated joints θ j , j = 1 to 6 are polynomial functions of the unactuated generalized variable q 1 , figures (1) and (2). Indeed, different researches [21], [22], [23] conclude this angle is always monotonically during a single support phase for most of walking gaits. So, this angle could be used instead of time for the bipedal robot.…”
Section: A Definition Of Actuated Joints Trajectoriesmentioning
confidence: 99%
“…Then the biped is underactuated in single support. In previous experiments, see for example, [7,14,15], researchers observed that for most of walking gaits of biped robots the ankle angle α of the stance leg changes absolutely monotonically during the single-support phase. Therefore, it is possible to use the angle variable α instead of time t as an independent variable during the single-support phase of the bipedal gait.…”
Section: Restrictions Of Motion Considered In Single Supportmentioning
confidence: 99%
“…Here it is worked with the control, the model and the reference trajectories to design walking bipedal gaits more fluid. See for example [7] where a biped with telescopic legs is studied, [8] where the famous dog Aibo from Sony is used to design biped gaits, [9] where an intuitive approach is developed for a biped locomotion or [10] where an accurate analysis of the gravity effects is made to give necessary and sufficient conditions to ensure a cyclic walking gait for a biped without feet.…”
Section: Introductionmentioning
confidence: 99%